Pengaruh Lingkungan Kerja, Motivasi Kerja, Dan Kepuasan Kerja Terhadap Kinerja Karyawan - Dina Fauzia Nurcholifah; Abdul Kodir Djaelani; Arini Fitria Mustapita (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
Abstract This study aims to determine the relationship between work environment variables, work motivation, and job satisfaction on employee performance. The location of this research is in the Tohu Srijaya UMKM Sector, Batu City. This research is a quantitative research. Data collection techniques using a questionnaire. The data analysis technique used in this research is using multiple linear regression analysis. Based on the results of data analysis, the variables of work environment, work motivation, and job satisfaction have a simultaneous effect on employee performance with positive and significant values. Partially, the variables of work environment, work motivation, and job satisfaction affect employee performance with positive and significant values. Keywords: work environment, work motivation, job satisfaction, employee performance